The organized mind thinking straight in the age of information overload - Levitin, Daniel J. (New York, New York Dutton, 2014)
Daniel J. Levitin, Ph.D., uses the latest brain science to demonstrate how people with "organized" minds excel--and how readers can use their methods to regain a sense of mastery over the way they organize their homes, workplaces,and lives
Information and conscientious organization -- Too much information, too many decisions : the inside history of cognitive overload -- The first things to get straight : how attention and memory work -- Organizing our homes : where things can start to get better -- Organizing our social world : how humans connect now -- Organizing our time : what is the mystery? -- Organizing information for the hardest decisions : when life is on the line -- Organizing the business world : how we create value -- What to teach our children : the future of the organized mind -- Everything else : the power of the junk drawer -- Appendix : Constructing your own fourfold tables
Includes bibliographical references (pages 397-481) and index
Keywords: Distraction (Psychology); Attention; Time management; Orderliness; Electronic books